The Effect of Breast Cancer Fatalism on Breast Cancer Awareness Among Turkish Women - Altintas, Hulya Kulakci (Journal of religion and health, 2017)
The aim of this study was to evaluate the effect of breast cancer fatalism and other factors on breast cancer awareness among Turkish women. This cross-sectional and comparative descriptive study was conducted with 894 women. Data were collected by Personal Information Form, Powe Fatalism Inventory and Champion’s Health Belief Model Scale. Seriousness, health motivation, BSE benefits and BSE self-efficacy perceptions of the women were moderate, and susceptibility and BSE barriers perceptions were low. It was determined that awareness of breast cancer of the women was affected by breast cancer fatalism, age, education level, employment status, marital status, family type, economic status, social assurance, menopause status, family history of cancer, family history of breast cancer, knowledge on BSE, source of information on BSE, performing of BSE, frequency of BSE performing, having a problem with breast, having a breast examination in hospital, feeling during breast examination by healthcare professional, sex of healthcare professional for breast examination and their health beliefs (p < .05). The results suggested that awareness of breast cancer of the women was affected by breast cancer fatalism. In providing breast cancer early diagnosis behaviors, it is recommended to evaluate fatalism perceptions and health beliefs of the women and to arrange educational programs for this purpose.